2017
DOI: 10.1016/j.gendis.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Neural EGF-like protein 1 (NELL-1): Signaling crosstalk in mesenchymal stem cells and applications in regenerative medicine

Abstract: Bone tissue regeneration holds the potential to solve both osteoporosis and large skeletal defects, two problems associated with significant morbidity. The differentiation of mesenchymal stem cells into the osteogenic lineage requires a specific microenvironment and certain osteogenic growth factors. Neural EGF Like-Like molecule 1 (NELL-1) is a secreted glycoprotein that has proven, both in vitro and in vivo, to be a potent osteo-inductive factor. Furthermore, it has been shown to repress adipogenic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 133 publications
0
22
0
2
Order By: Relevance
“…Studies have shown the multi-differentiation potentials of OAT-PFs as MSC [54]. Our work suggests that OAT-produced growth factors interacting with multiple signaling pathways (TGFβ/Wnt/Ca+/FGF/Notch/MAPK/PI3K) that support repair mechanisms such as adipogenesis, osteogenesis, myogenesis, chondrogenesis, neurogenesis and angiogenesis [31][32][33][37][38][39][40][41][42][43][44][45][46]. Furthermore, we have demonstrated a depot specific triglyceride composition of OAT, for example, stearic acid (18:0 FA), a stable waxy solid fat.…”
Section: Speculations From Current Studymentioning
confidence: 68%
See 1 more Smart Citation
“…Studies have shown the multi-differentiation potentials of OAT-PFs as MSC [54]. Our work suggests that OAT-produced growth factors interacting with multiple signaling pathways (TGFβ/Wnt/Ca+/FGF/Notch/MAPK/PI3K) that support repair mechanisms such as adipogenesis, osteogenesis, myogenesis, chondrogenesis, neurogenesis and angiogenesis [31][32][33][37][38][39][40][41][42][43][44][45][46]. Furthermore, we have demonstrated a depot specific triglyceride composition of OAT, for example, stearic acid (18:0 FA), a stable waxy solid fat.…”
Section: Speculations From Current Studymentioning
confidence: 68%
“…Angiopoietin (ANGPT4) [39] angiogenesis Osteoglycin (OGN) [40] bone formation Neural EGF-like protein (NELL1) [41] bone formation TGFβ family 1 [42] (TGFB2, BMP3, 7,11) and Latent TGFβ binding protein 1…”
Section: Up-regulated Growth Factor (Multi-function 1) Known Functionmentioning
confidence: 99%
“…The effect of Nell-1 gene on osteogenesis has been verified through in vivo and in vitro study, but the mechanism of Nell-1’s function on BMSCs remains unclear. Studies suggested that Nell-1 protein acted on various signaling pathway including Wnt signaling pathway, hedgehog signaling pathway, and BMP2 signaling pathway ( Shen et al, 2016 ; Pakvasa et al, 2017 ; Li et al, 2018 ). Zhang found that Nell-1 protein induced phosphorylation of Runx2 ( Zhang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed integrinβ1 protein can mediate cell adhesion and integrate signals from a variety of cytokines and other growth factor. NELL-1(potent osteo-inductive factor) binding to integrinβ1 activates an intracellular signaling cascade that promotes cell adhesion, proliferation, and osteogenic differentiation 72. It can be seen that the expression of both integrinβ1 and vinculin manifested more abundant expression (much stronger fluorescent intensity) on the (GO-CS)20 scaffold in comparison to the pure PU scaffold after 4 h of culturing.The much stronger fluorescent intensity of integrinβ1 and vinculin expression on (GO-CS)20scaffold suggest the coated scaffold shows stronger cell adhesion, which indicate (GO-CS)20 scaffold holds stronger potential for tissue regeneration than the PU control sample 72.…”
mentioning
confidence: 99%
“…NELL-1(potent osteo-inductive factor) binding to integrinβ1 activates an intracellular signaling cascade that promotes cell adhesion, proliferation, and osteogenic differentiation 72. It can be seen that the expression of both integrinβ1 and vinculin manifested more abundant expression (much stronger fluorescent intensity) on the (GO-CS)20 scaffold in comparison to the pure PU scaffold after 4 h of culturing.The much stronger fluorescent intensity of integrinβ1 and vinculin expression on (GO-CS)20scaffold suggest the coated scaffold shows stronger cell adhesion, which indicate (GO-CS)20 scaffold holds stronger potential for tissue regeneration than the PU control sample 72. CCK-8 assay proliferation after 1, 3 and 5 days of culture, n=5 per group; (*), p < 0.05 when compared with blank group, (#), p < 0.05 when compared with PU control group.The proliferation of cells was qualitatively determined by CCK-8 assay, seeFigure 10.…”
mentioning
confidence: 99%